Organizational capabilities and accrual accounting adoption in Indonesian municipalities: the moderating effect of organizational culture - Aswar, Khoirul (2020)
Based on the accrual accounting system trend, in 2010 the Indonesian government had introduced the accrual accounting system. The system was fully adopted in 2015 through the Government Regulation No. 71 of 2010. Thus, the aim of this study is to investigate the level of adoption of accrual accounting in Indonesian municipalities. Using institutional theory, this study examines the relationship of organizational capabilities on the level of accrual accounting adoption. It also examines the moderating effect of organizational culture on the relationship between organizational capabilities and the level of accrual accounting adoption. The study employs a questionnaire survey and uses a cluster sampling technique to collect data from 273 head of accounting sections with a self-administered questionnaire. Out of the 273 questionnaires distributed, 212 were returned. However, only 202 responses representing a 77% response rate were valid for analysis. The results revealed that level of accrual accounting adoption is moderate (77.85%). The results also showed that top management support and quality of information technology influence the level of accrual accounting adoption, whereas adequate training program, effective communication, implementation cost and effective project leader do not. In addition, the result showed that the organizational culture moderates the relationship between top management support, adequate training program, implementation cost, and the level of accrual accounting adoption; and it does not moderate the relationship between quality of information technology, effective communication, project leader and the level of accrual accounting adoption. This study contributed and extended the organizational capabilities affecting the level of accrual accounting adoption only in municipalities. Therefore, further studies could be conducted to include local government in the whole of Indonesia. Also, future studies may adopt other methods, such as interviewing the local government, that can explore more deeply the main motivation that drives the level of accrual accounting adoption in Indonesia.